2003
DOI: 10.1046/j.1523-1755.2003.00859.x
|View full text |Cite
|
Sign up to set email alerts
|

Modeling study of human renal chloride channel (hCLC-5) mutations suggests a structural-functional relationship

Abstract: These results demonstrate a crucial role for the interaction between the two subunits at the interface of the homodimeric hCLC-5.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 31 publications
3
56
0
Order By: Relevance
“…Each subunit has its own pore and 17 α-helices inserted into the plasma membrane, with an anti-parallel orientation that brings together residues responsible for anion selectivity [21]. Based on these data, a model for human ClC-5 has been established, allowing analysis of the role of 15 non-truncating mutations (14 missense and one in-frame deletion) of CLCN5 [22]. This analysis revealed that none of these mutations involves the selectivity filter, but that most of them (12/15) are clustered at the interface of the two subunits of the homodimeric channel [22].…”
Section: Recent Developments and Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Each subunit has its own pore and 17 α-helices inserted into the plasma membrane, with an anti-parallel orientation that brings together residues responsible for anion selectivity [21]. Based on these data, a model for human ClC-5 has been established, allowing analysis of the role of 15 non-truncating mutations (14 missense and one in-frame deletion) of CLCN5 [22]. This analysis revealed that none of these mutations involves the selectivity filter, but that most of them (12/15) are clustered at the interface of the two subunits of the homodimeric channel [22].…”
Section: Recent Developments and Perspectivesmentioning
confidence: 99%
“…Based on these data, a model for human ClC-5 has been established, allowing analysis of the role of 15 non-truncating mutations (14 missense and one in-frame deletion) of CLCN5 [22]. This analysis revealed that none of these mutations involves the selectivity filter, but that most of them (12/15) are clustered at the interface of the two subunits of the homodimeric channel [22]. The functional evaluation of other naturally occurring mutants is necessary in order to define the role of conserved domains for ClC-5 function and/or trafficking: a case in point is a C-terminus internalization motif, resembling the PY motif that is essential for the internalization and degradation of the epithelial sodium channel, ENaC [23].…”
Section: Recent Developments and Perspectivesmentioning
confidence: 99%
“…DNA samples from 87 unrelated healthy Japanese individuals (68 females, 19 males) with 155 alleles of the CLCN5 gene did not reveal this nucleotide change, indicating that the mutation is not due to a common single nucleotide polymorphism. In the CLC-5 protein, this amino acid substitution is located in helix J, one of 18 α-helices [9]. Genomic analysis of the patient’s mother revealed that she was heterozygous for the mutation.…”
Section: Resultsmentioning
confidence: 99%
“…The human CLCN5 gene, which is located on chromosome Xp11.22, has a coding region of 2,238 bp that consists of 11 exons and encodes the 746 amino acid protein, CLC-5 [7]. Prokaryotic CLC-5 was found to form a homodimeric structure by X-ray analysis [8] and a similar structural model was suggested for the human counterpart in which each subunit consists of 18 α-helices [9]. Heterologous expression of wild-type (WT) CLC-5 in Xenopus oocytes revealed that CLC-5 conducts outwardly rectifying chloride currents and similar expression of disease-associated CLC-5 mutants demonstrated markedly reduced or absent currents [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation